Reindeer grazing history determines the responses of subarctic soil fungal communities to warming and fertilization. Issue 2 (6th August 2021) - Ahonen, Saija H. K.; Ylänne, Henni; Väisänen, Maria; Ruotsalainen, Anna Liisa; Männistö, Minna K.; Markkola, Annamari; Stark, Sari
Summary: Composition and functioning of arctic soil fungal communities may alter rapidly due to the ongoing trends of warmer temperatures, shifts in nutrient availability, and shrub encroachment. In addition, the communities may also be intrinsically shaped by heavy grazing, which may locally induce an ecosystem change that couples with increased soil temperature and nutrients and where shrub encroachment is less likely to occur than in lightly grazed conditions. We tested how 4 yr of experimental warming and fertilization affected organic soil fungal communities in sites with decadal history of either heavy or light reindeer grazing using high‐throughput sequencing of the internal transcribed spacer 2 ribosomal DNA region. Grazing history largely overrode the impacts of short‐term warming and fertilization in determining the composition of fungal communities. The less diverse fungal communities under light grazing showed more pronounced responses to experimental treatments when compared with the communities under heavy grazing. Yet, ordination approaches revealed distinct treatment responses under both grazing intensities. If grazing shifts the fungal communities in Arctic ecosystems to a different and more diverse state, this shift may dictate ecosystem responses to further abiotic changes. This indicates that the intensity of grazing cannot be left out when predicting future changes in fungi‐driven processes in the tundra.